Purification and Characterization of a New Plant Endopeptidase Isolated from Latex of Asclepias fruticosa L. (Asclepiadaceae) - Trejo, Sebastián Alejandro (2001)
Asclepias fruticosa L. is a small shrub containing latex with proteolytic activity. The crude extract (latex diluted 1:250 and ultracentrifuged) contained 276 μg of protein/mL and the proteolytic activity reached 1.2 caseinolytic U/mL. This enzyme preparation was very stable even after 2 hours at 45°C, but was quickly inactivated after 5 minutes at 80°C. Chromatographic purification was achieved by FPLC using a cation exchanger (SP-Sepharose FF). Thus, a unique proteolitically active fraction could be isolated, being homogeneous by bidimensional electrophoresis and mass spectrometry (Mr = 23,652). The optimum pH range was achieved at 8.5–10.5. The enzyme activity was completely inhibited by specific cysteine peptidases inhibitors. Isoelectric focusing followed by zymogram showed the enzyme had a pI greater than 9.3. The N-terminus sequence (LPDSVDWREKGVVFPIRNQGK) shows a great deal of similarity to those of the other cysteine endopeptidases isolated from latices of Asclepiadaceae even when a high degree of homology could be observed with other plant cysteine endopeptidases.